2007
DOI: 10.1016/j.juro.2007.03.101
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence of Perioperative Chemotherapy for Stage III Bladder Cancer 1998 to 2003: A Report From the National Cancer Data Base

Abstract: Perioperative chemotherapy is underused in the management of surgically resectable stage III transitional cell carcinoma of the bladder. This finding may reflect a delay in implementing the results of recently reported randomized trials, a low incidence of referrals by urologists for chemotherapy and/or confidence in salvage chemotherapy as an equivalent alternative. Further followup will determine if this treatment pattern changes in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 220 publications
(127 citation statements)
references
References 13 publications
3
119
0
5
Order By: Relevance
“…52 Despite the evidence supporting the use of neoadjuvant chemotherapy, a review of more than 7000 patients treated for stage III bladder cancer in the United States between the years 1998 and 2003 showed that only 1.2% of patients received neoadjuvant treatment, and only 10.4% received adjuvant treatment. 193 The evidence for adjuvant therapy is primarily based on a meta-analysis of 6 small trials, totaling about 600 patients; although this study suggested a 25% relative decrease in the risk of death with chemotherapy compared with no therapy, the number of patients was insufficient to recommend adjuvant treatment. 194 Unfortunately, large trials evaluating adjuvant treatment have not been performed, and the smaller studies included in the above meta-analysis have been criticized for methodologic flaws.…”
Section: Urinary Diversionmentioning
confidence: 97%
“…52 Despite the evidence supporting the use of neoadjuvant chemotherapy, a review of more than 7000 patients treated for stage III bladder cancer in the United States between the years 1998 and 2003 showed that only 1.2% of patients received neoadjuvant treatment, and only 10.4% received adjuvant treatment. 193 The evidence for adjuvant therapy is primarily based on a meta-analysis of 6 small trials, totaling about 600 patients; although this study suggested a 25% relative decrease in the risk of death with chemotherapy compared with no therapy, the number of patients was insufficient to recommend adjuvant treatment. 194 Unfortunately, large trials evaluating adjuvant treatment have not been performed, and the smaller studies included in the above meta-analysis have been criticized for methodologic flaws.…”
Section: Urinary Diversionmentioning
confidence: 97%
“…4,5 Despite the survival improvement established in randomized trials with the use of neoadjuvant methotrexate, vinblastine, doxorubicin, plus cisplatin (MVAC) or cisplatin, methotrexate, plus vinblastine 5 (CMV), concerns regarding the balance between the toxicity and efficacy of these regimens has contributed, at least in part, to the poor uptake of neoadjuvant chemotherapy. [4][5][6] In 2000, the results from a randomized phase 3 trial were published comparing gemcitabine plus cisplatin (GC) with standard MVAC in patients with metastatic bladder cancer. 7,8 GC was associated with similar efficacy compared with MVAC, albeit with less toxicity, leading to the adoption of this regimen as among the most commonly used systemic treatments for patients with metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…A previous analysis from the UTUC collaboration, including 542 high risk UTUC patients (T3,4 and/or n+), could not identify a survival advantage of the use of adjuvant chemotherapy after RnU, possibly due to the underutilization of systemic chemotherapy and administration of adjuvant chemotherapy only in advanced stage of the disease (10). The underutilization of systemic chemotherapy is not surprising, considering the low incidence of peri-operative chemotherapy reported in bladder cancer and the absence of randomized trials demonstrating a survival benefit in patients with UTUC (11).…”
Section: Discussionmentioning
confidence: 99%